Clinical impact of healthcare-associated respiratory syncytial virus in hospitalized adults. (14th March 2023) - Hill-Ricciuti, Alexandra; Walsh, Edward E.; Greendyke, William G.; Choi, Yoonyoung; Barrett, Angela; Alba, Luis; Branche, Angela R.; Falsey, Ann R.; Phillips, Matthew; Finelli, Lyn; Saiman, Lisa
Abstract: Objective: To describe the clinical impact of healthcare-associated (HA) respiratory syncytial virus (RSV) in hospitalized adults. Design: Retrospective cohort study within a prospective, population-based, surveillance study of RSV-infected hospitalized adults during 3 respiratory seasons: October 2017–April 2018, October 2018–April 2019, and October 2019–March 2020. Setting: The study was conducted in 2 academically affiliated medical centers. Patients: Each HA-RSV patient (in whom RSV was detected by PCR test ≥4 days after hospital admission) was matched (age, sex, season) with 2 community-onset (CO) RSV patients (in whom RSV was detected ≤3 days of admission). Methods: Risk factors and outcomes were compared among HA-RSV versus CO-RSV patients using conditional logistic regression. Escalation of respiratory support associated with RSV detection (day 0) from day −2 to day +4 was explored among HA-RSV patients. Results: In total, 84 HA-RSV patients were matched to 160 CO-RSV patients. In HA-RSV patients, chronic kidney disease was more common, while chronic respiratory conditions and obesity were less common. HA-RSV patients were not more likely to be admitted to an ICU or require mechanical ventilation, but they more often required a higher level of care at discharge compared with CO-RSV patients (44% vs 14%, respectively). Also, 29% of evaluable HA-RSV patients required respiratory support escalation; these patients were older and more likely to have respiratory comorbidities, to have been admitted to intensive care, and to die during hospitalization. Conclusions: HA-RSV in adults may be associated with escalation in respiratory support and an increased level of support in living situation at discharge. Infection prevention and control strategies and RSV vaccination of high-risk adults could mitigate the risk of HA-RSV.